A Study to Relate Sagittal Condylar Path and Horizontal Incisal Path with Bilateral Balanced Occlusion in Edentulous Subjects - D., Krishna Prasad; Prasad, B. Rajendra; D., Anupama Prasad (Journal of Health and Allied Sciences NU, 2020)
Introduction Bilateral balanced occlusion is achieved when there is equilibrium on both sides of the prosthesis, due to the simultaneous contact of the artificial teeth in centric and eccentric occlusion. One of the areas in which research is lacking is the relation between sagittal condylar path (CP) and horizontal incisal path (IP) with optimal balanced occlusion.Materials and Methods Semiadjustable Articulator Artex Arcon AP with Rotofix facebow, 40 µ Bosch articulating paper of red and blue color, protractor, centric and protrusive interocclusal plaster records were used for the study on 50 completely edentulous subjects. Teeth arrangement was done with optimal balanced occlusion, and the numbers of contacts were recorded in centric relation and eccentric positions. Statistical analysis was done by using student’s t test and Karl Pearson coefficient correlation.Results The average sagittal CP was 30.38° in the age group of 40 to 55 years and 32.58° in the age group of 56 to 70 years, and the average horizontal IP was 15.79° in the age group of 40 to 55 years and 16.04° in the age group of 56 to 70 years.Statistically significant results were found between sagittal CP, horizontal IP with bilateral balanced occlusion in the age group of 40–55 years.Conclusion Statistically significant relations were found in balanced occlusion between waxed up denture on articulator, processed denture on articulator and processed denture on articulator after selective grinding. Balanced occlusion is more predictable in a younger group of individuals.
Keywords: sagittal condylar path; horizontal incisal path; bilateral balanced occlusion